Selected Factors Related to Weight Loss in Post-operative Colorectal Cancer Patients - Buakrai, monnaphorn (NU Journal of Nursing and Health Sciences, 2025)
This study is a retrospective study research. To study the correlation factors for weight loss in patients post-operation colorectal cancer from the selected variables are as follows: age, American Society of Anesthesiologist Physical Status classification, Preoperative albumin serum values, stage of Colorectal cancer, Neoadjuvant Therapy, Length of time to Start oral feeding after surgery, and complications post-operation colorectal cancer. The sample group used in the study medical records of colorectal cancer patients who received treatment after surgery at the surgical inpatient department of a university hospital in the lower northern region during the period from 1 January 2018 to 31 December 2023. In all, 200 case individuals were purposively sampled as the sample, using the recording form the information on patients who have undergone surgery for colorectal cancer. Which is divided into 3 parts: 1) Personal information record form 2) Medical history record form and 3) Recording nutritional status data. The data that were analyzed using descriptive statistics: number, percentage, mean and standard deviation. To find the correlation between selected factors and weight loss after colorectal cancer surgery by using Spearman’s rank and point biserial correlation coefficient. The results found that a correlation between the time starting postoperative oral feeding and complications post-operation colorectal cancer with weight loss after colorectal cancer surgery was statistically significant (rs = 0.191, p = 0.007 and rpb = 0.200, p = 0.004, respectively). The relationships found were low and in the same direction. On the contrary, in other selected factors no relationship was found with weight loss after colorectal cancer surgery. The results of this research are used as basic information for nursing planning. To prevent weight loss in patients after colorectal cancer surgery.